2017
DOI: 10.1186/s12885-017-3888-y
|View full text |Cite
|
Sign up to set email alerts
|

Pricing appraisal of anti-cancer drugs in the South East Asian, Western Pacific and East Mediterranean Region

Abstract: BackgroundGlobally, cancer is one of the leading causes of mortality. High treatment cost, partly owing to higher prices of anti-cancer drugs, presents a significant burden on patients and healthcare systems. The aim of the present study was to survey and compare retail prices of anti-cancer drugs between high, middle and low income countries in the South-East Asia, Western Pacific and Eastern Mediterranean regions.MethodsCross-sectional survey design was used for the present study. Pricing data from ten count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Their study showed highest cost variation in hormonal anticancer drugs (714.24%) and lowest variation with targeted anticancer drugs (5.56%) in India 8. A study by Salmasi S et al, also concluded great variation in pricing of anticancer drugs in other countries like in South East Asian, Western Pacific and East Mediterranean Region 9.…”
mentioning
confidence: 92%
“…Their study showed highest cost variation in hormonal anticancer drugs (714.24%) and lowest variation with targeted anticancer drugs (5.56%) in India 8. A study by Salmasi S et al, also concluded great variation in pricing of anticancer drugs in other countries like in South East Asian, Western Pacific and East Mediterranean Region 9.…”
mentioning
confidence: 92%
“…We identified only one study directly comparing publicly listed prices for 22 anticancer drugs; the authors found prices in Lebanon tended to be among the lowest compared with the other eight countries (seven Asian countries and Egypt) in that study. 36 There are indications of cancer drug prices decreasing since 2011 in Lebanon, including through procurement negotiations led by the MOPH. 37 More recently, the government of Jordan reduced in June 2019 the list prices of > 1,000 drugs, including a 10% reduction for cancer drugs.…”
Section: Resultsmentioning
confidence: 99%
“…We identified one study protocol referring specifically to the costs of pediatric cancer care, and that was in Jordan. 79 Other sources referred to the overall financial burden of cancer care, for example, from the perspective of the Lebanese MOPH (cancer drugs cost USD 140 million over 3 years 36 ); but the way the data were presented did not allow disaggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-cancer medicines are usually expensive [6] and cause financial distress to the patients, society, and the country. Studies have reported significant variation in the prices of the same anti-cancer medicines across different countries (up to 388% variation) [7,8] and within a country (up to 714% variation) [9].…”
Section: Introductionmentioning
confidence: 99%